Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice—A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice - A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Ecological Validity in Exercise Neuroscience Research: A Systematic Investigation - Chang, M.; Büchel, Daniel; Reinecke, K.; Lehmann, T.; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Abstract The present study examines if the neural signature of information processing in mental rotation tasks is moderated by stimulus characteristics (e.g., body‐related vs. non‐body‐related stimuli). In the present experiment, stimulus sets of human figures (back view; left vs. right arm abduction) and alphanumeric characters (‘R’; normal vs. mirrored view) were scrutinized with event‐related potentials (ERPs) in the electroencephalography (EEG). Participants had to judge parity between an upright (0° orientation) and a comparison stimulus (stimulus disparity; 0°, 45°, 90°, 135° or 180°). There was a main effect of stimulus disparity for the behavioural (response time and error rates), as well as for the neural data (rotation‐related negativity, RRN). The interaction of stimulus disparity and stimulus type was significant for the RRN, but not for the response time. Lower RRN amplitudes for letters indicate a more pronounced use of alternative processes (e.g., memory retrieval), which seems to be reflected in higher N350 amplitudes. Moreover, the increase of the RRN amplitude and the increase in response time as a function of disparity were positively correlated. Task differences were evident for several ERP components (i.e., N150, P150 and N250), being independent of disparity, which might reflect differences in early and late object cognition prior to the mental rotation process itself. This might be associated with the task‐dependent activation of embodied cognition processes in mental rotation tasks.
Keywords: General Neuroscience

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Keywords: General Neuroscience